The development of spatial ability among basic education students and its relationship to their engineering thinking (Journal of the College of Basic Education, 2022)
The present study aims at knowing: the significance of the statistical differences in each of the spatial ability and geometric thinking of students in the basic education stage according to the basic (fifth, eighth) grades, and the relationship between the spatial ability of students in the basic education stage and their geometric thinking, the study sample consisted of (400) students in the basic education (fifth, and eighth) grades in Baghdad for the academic year (2016 – 2017), was selected (205) students of the fifth grade, and (195) students of the eighth grade, the researcher prepared two tools, the first was to measure spatial ability of students in the eighth grade consisted of (20) items, (15) the first items to measure spatial ability of students in the fifth grade, the second was to measure geometric thinking of students in the eighth grade consisted of (30) items, (20) the first items to measure geometric thinking of students in the fifth grade, it has been verified sincerity,and the reliability of each tool. The results are analyzed using an equation t-test for two independent samples. The study found that: there were significant statistical differences at (0.05) in each of the spatial ability and geometric thinking according to the basic (fifth, eighth) grades, and there were a positive correlation between the scores of the spatial ability test